Wavelength-tunable thulium-doped fiber laser by employing a self-made Fabry–Perot filter. (11th May 2017) - Wang, Y P; Ju, Y L; Wu, C T; Liu, W; Yang, C
Abstract: In this demonstration, we proposed a novel wavelength-tunable thulium-doped fiber laser (TDFL) with a self-made Fabry–Perot (F–P) filter. When the F–P filter was not inserted, the maximum output power of 11.1 W was achieved when the pump power was 70.2 W. The corresponding optical-to-optical conversion efficiency was 15.8% and the slope efficiency was 22.1%. When the F–P filter was inserted, the output wavelength could be tuned from 1952.9 to 1934.9 nm with the change of cavity length of F–P filter which was fixed on a piezoelectric ceramic transducer (PZT) controlled by the voltage applied to it. The full width at half maximum (FWHM) was no more than 0.19 nm. Furthermore, the wavelength fluctuations of the tunable fiber laser were kept within ±0.2 nm.